At risk for dyslexia : the role of phonological abiliteis, letter knowledge, and speed of serial naming in early intervention and diagnosis. - Eleveld, Marianne, ....- (Antwerpen : Garant, 2005)
Dyslexia is all impairment characterized by life-long problems in reading and/or spelling, and with negative emotional, behavioral, and educational side-effects. Early identification and early intervention are necessary to minimize or even prevent reading disabilities and accompanying problems of children at risk for dyslexia. In the first chapters of this book, the current scientific knowledge in the domains of early identification and early intervention of dyslexia will be described in detail. Many studies over the last decades have demonstrated the importance of phonological awareness in predicting dyslexia. Recently, more insight in the independent role of speed of serial naming in predicting dyslexia has been established. Previous intervention studies have shown that phonological awareness can be trained successfully in kindergarten. Not only direct effects on the trained ability have been reported, but also transfer effects on reading and spelling abilities. The book continues with a discussion of a Dutch longitudinal intervention study with kindergarten children at familial risk for dyslexia. Outcomes of this study appear to deviate from findings in other intervention studies. Implications for educational policy and practice in the Netherlands will be discussed. This book provider interesting information about dyslexia in the Dutch situation, not only for researchers in the field of dyslexia, but also for students, experts in the domains of diagnosis and treatment of children with learning disabilities, and other persons interested in dyslexia.
This is the commercial edition of the corresponding dissertation University of Groningen (The Netherlands), 6th of June 2005
Keywords: Dyslexie